Solubility of CO2 in aqueous sodium Î²-alaninate: Experimental study and modeling using Kent Eisenberg model - Aftab, A. (Institution of Chemical Engineers, 2018)
In this work, the equilibrium solubility of CO2 in aqueous solution of 10, 20, and 30 wt sodium Î²-alaninate (Na-Î²ala) was investigated using high pressure solubility cell. The solubility experiments were carried out at temperatures 303.15, 313.15, and 333.15 K and over CO2 partial pressure ranging from 2 to 25 bar. Experimental results showed that with the increase in Na-Î²ala concentration and temperature of the system, CO2 loading decreases. Whereas, the CO2 loading increases by increasing the partial pressure of CO2. Furthermore, a modified KentâEisenberg model was used to correlate CO2 solubility data as a function of temperature, concentration and CO2 partial pressure. An average absolute deviation of 12.8 was obtained between the experimental and model correlated data, which indicated the good correlation capability of the applied model. Â© 2017 Institution of Chemical Engineers